(untitled) (Bioresearch Communications, 2022)
A total of 9 fungal species belonging to four genera were found to be associated with coral skeleton collected from Saint Mar tin’s Island, Bangladesh. The isolated fungi were Arthrinium Kunze, Aspergillus flavus Link, Fusarium nivale (Fr.) Sorauer, F. oxysporum Schltdl., F. sambucinum Fuckel, F. semitectum Berk. & Ravenel, F. stoveri Booth, F. trichothecioides Wollenw and Penicillium Link. The genus Fusarium was predominant among the associated fungi. This is the first report of fungal association with solid calcium carbonate substrate like coral skeleton from Bangladesh. Fusarium sambucinum and F. stoveri are first time recorded from Bangladesh. Bioresearch Commu. 9(1): 1203-1207, 2023 (January)